Impact of Profitability, Leverage, Capital Intensity, Firm Size, and Firm Age on Tax Avoidance - Gowira, David; Haryono, Haryono; Dosinta, Nina Febriana (Jurnal Akuntansi dan Perpajakan, 2024)
Indonesia's primary source of state revenue is taxes and is used to support economic growth to achieve the vision of "Golden Indonesia 2045". The challenge in collecting tax revenues is the act of tax avoidance by companies. This research wants to study whether the tax avoidance of basic materials companies on the Indonesia Stock Exchange from 2018 to 2022 is affected by factors such as profitability, leverage, capital intensity, company size, and company age. Ninety-six basic materials companies are the population in this study. This quantitative research uses financial reports through purposive sampling with a total sample of two hundred and ninety-five data. The findings in this study show that the tax avoidance is significantly positively influenced by profitability which is proxied by return on assets, while the tax avoidance is significantly negatively influenced by company size. On the other hand, the tax avoidance is not significantly influenced by leverage, capital intensity, and company age. These results imply that company management is encouraged to avoid taxes to meet the profit level targets set by shareholders, but remains careful to maintain the company's good reputation.